Forsaken - Bowden, Oliver (Assassin's creed, 2012)
London. Haytham Kenway has been taught to use a sword from the age he was able to hold one. When his family's house is attacked - his father murdered and his sister taken by armed men - Haytham defends his home the only way he can: he kills. With no family, he is taken in by a mysterious tutor who trains him to become a deadly killer. Consumed by his thirst for revenge, Haytham begins a quest for retribution, trusting no one and questioning everything he has ever known.